Implementation of Microsoft SQL Server using ‘AlwaysOn’ for High Availability and Disaster Recovery without Shared Storage - Zulqarnain Hayat; Tariq Rahim Soomro (International Journal of Experiential Learning & Case Studies)
It is important for any organization to handle increase in data; normally this is the job of the DBA in organization to take care of this data growth, along with its protection and its availability.  High availability of data is also most important for organizations, for that purpose, shared storage is usually the solution, for example, SAN or NAS storage as Microsoft Cluster Database instances. Mostly Organization does not have shared storage in their infrastructure, which was required for Microsoft cluster SQL database instance; due to that they used other native methods to implement like log shipping or database mirroring, which was not efficient method for high-availability and disaster-recovery solution.  After that, Microsoft introduced native method called SQL AlwaysOn method that could be implemented without using SAN and NAS storage method to implement high availability and disaster recovery without using shared storage.  SQL AlwaysOn option is using only Microsoft cluster service and shared folder between the nodes. This paper written for DBA and System Administrators; and is implementation of Microsoft SQL Database tier step by step.